2012
DOI: 10.1177/000313481207800938
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Outcomes of Iatrogenic Colon Perforations at a Community Teaching Hospital

Abstract: Despite the growing expertise in colonoscopy, it remains subject to complications. The previously published rate of colonoscopic perforation is 0.82 per 1000 examinations. The objective of this study was to describe the experience and management of colonoscopic perforations. A retrospective review of cases from a database of surgical complications was searched for perforations postcolonoscopy from January 1, 2001, to December 31, 2010 at a 527-bed community teaching hospital. Eighteen patients were identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…If colon perforation develops, panperitonitis, acute abdominal compartment syndrome, ostomy creation, or death may develop [ 4 ]. The most common site of colon perforation is the sigmoid colon [ 5 ]. In the present study, we also found that 70.4% of the colon perforations developed at the sigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
“…If colon perforation develops, panperitonitis, acute abdominal compartment syndrome, ostomy creation, or death may develop [ 4 ]. The most common site of colon perforation is the sigmoid colon [ 5 ]. In the present study, we also found that 70.4% of the colon perforations developed at the sigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
“…Published series reported high mortality among patients with colonoscopic perforation [ 3 - 6 ]. Early exploratory laparotomy with primary closure or bowel resection has been the standard treatment of colonoscopic perforation; however, relatively high morbidity and mortality rates were reported [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%